2019
DOI: 10.5539/ass.v15n11p60
|View full text |Cite
|
Sign up to set email alerts
|

Identity Options and Cultural Representations in English Textbooks Used in Cambodia

Abstract: Language textbooks play an important role in bridging learners’ understanding between the source culture and target culture. This study explores how the Cambodian and foreign characters are produced and how the source and target cultures are represented in three English language textbooks published by the Cambodian Ministry of Education, Youth and Sport (MoEYS). The data were collected from textbook passages, exercises and images presented in the textbooks and the data were analyzed based on the emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This method consists of a systematic procedure that can be employed to infer the texts or transcripts of human interaction validly. It classifies texts into applicable and controllable data (Li et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method consists of a systematic procedure that can be employed to infer the texts or transcripts of human interaction validly. It classifies texts into applicable and controllable data (Li et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the study on cultural representation in English textbooks used in Cambodia is rarely conducted. The past study has explored the identity choices and cultural depictions in English textbooks utilized in Cambodia (e.g., Li et al, 2019). The result of this study showed that the contents of the books, especially the images and people in the dialogue or conversation in the books are mostly concerned with Japanese culture in terms of foreign culture due to the fact that Japan is one of the main educational supporters.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main reasons to represent local culture in EFL textbooks for junior high schools in Indonesia which include promoting a sense of familiarity among junior high school students in learning English as well as strengthening the national aspect (Mahmud, 2019). Thus, English textbooks used by educators must consider the choice of diverse identities and cultural representations (Li, Dong, & Duan, 2019) According to previous research, textbooks are one of the fundamentals for achieving culturaleducational values and the development needs of human life. As a result, the gap in this study focuses on the study of cultural values in textbooks, which are understood through the topics or themes found in each chapter of the textbook.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on English as a Foreign Language (EFL) textbooks have concentrated on how cultural content is portrayed in the textbooks over the last five years (Arslan, 2016;Hodkinson, Ghajarieh, & Salami, 2018;Kiss, 2017;Li, Dong, & Duan, 2019;Sahraee, 2018;Su, 2016;Teo & Kaewsakul, 2016). The research body is primarily situated in Asia (e.g., China, Iran, Taiwan, Cambodia, Thailand) and Europe (e.g., Turkey).…”
Section: Introductionmentioning
confidence: 99%